1998
DOI: 10.1021/om971028v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Ketonyl Palladium(II) and Platinum(II) Complexes with Nitrogen-Donor Ligands. Crystal Structure of [Pt{CH2C(O)Me}2(bpy)]

Abstract: Complexes [MCl2L2] (M = Pd, Pt; L2 = 2,2‘-bipyridine (bpy) or Me2N(CH2)2NMe2 (tmeda)) react with ketones MeC(O)R (R = Me, Et) in the presence of bases (Ag2O or M‘OH (M‘ = Na, K)) to give the new types of ketonyl palladium(II) and platinum(II) complexes [M{CH2C(O)R}ClL2] (M = Pd, L2 = N,N,N‘,N‘-tetramethylethylenediamine = tmeda; M = Pt, L2 = 2,2‘-bipyridine = bpy) and [Pt{CH2C(O)R}2L2] (R = Me, Et, L2 = bpy). Oxidative addition of chloroacetone on [Pt(dba)2] in the presence of bpy also yields [Pt{CH2C(O)R}ClL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 44 publications
5
56
0
Order By: Relevance
“…This was attributedtoastronger weakening of the particle surface chargei np olar solvents than in less-polar ones. The existence of enolate groups bound on metal oxide surfaces [54,55] or on organometallic complexes [56] of Pt and Pd has been reported in the literature on the basis of IR spectroscopy measurements of acetone. [17] They showed that the presence of chaotropic anions, which have high polarizability, resulted in smaller and more stable particles compared with particless ynthesized in the presence of smalla nions with al ow polarizability (cos- motropes).…”
Section: Discussionmentioning
confidence: 98%
“…This was attributedtoastronger weakening of the particle surface chargei np olar solvents than in less-polar ones. The existence of enolate groups bound on metal oxide surfaces [54,55] or on organometallic complexes [56] of Pt and Pd has been reported in the literature on the basis of IR spectroscopy measurements of acetone. [17] They showed that the presence of chaotropic anions, which have high polarizability, resulted in smaller and more stable particles compared with particless ynthesized in the presence of smalla nions with al ow polarizability (cos- motropes).…”
Section: Discussionmentioning
confidence: 98%
“…If some condensation is mediated by palladium, we suspect that this occurs as depicted in Scheme (i.e., before the complete transformation of the hydridopalladium enolate into the corresponding aldehyde). Indeed, the formation of palladium enolates from carbonyl compounds requires Pd II complexes 24,25 …”
Section: Aryl‐substituted Epoxidesmentioning
confidence: 99%
“…A range of synthetic methodologies have been used to form these M–ketonyl derivatives,18, 20 for example, oxidative addition to organometallic compounds of α‐halogen carbonyl compounds21 or epoxides,22 transmetallation reactions promoted by Hg salts18, 23 or reactions of main‐group enolates with electrophilic metal centers 19a. 24 Other methodologies involve reactions of carbonyl compounds with metal‐hydroxide25 or metal‐chloride complexes in the presence of bases, such as Ag 2 O, KOH, and NaOH 20c. 26…”
Section: Introductionmentioning
confidence: 99%